Bio-consolidation of cracks in masonry cement mortars by Acinetobacter sp. SC4 isolated from a karst cave. (July 2019) - Li, Mengmeng; Fang, Chaolin; Kawasaki, Satoru; Huang, Minsheng; Achal, Varenyam
Abstract: Microbially induced carbonate precipitation (MICP) is one of techniques for consolidation of cementitious materials; however, limited biodiversity and inadequate information on its application suggests further extensive research in this area. In this study, bacteria with ability to precipitate carbonate, preferably CaCO3, were isolated from Yixing Shanjuan Cave, China after analyzing bacterial diversity using Illumina MiSeq sequencing the V3-V4 region of 16S rRNA gene. A total of 58, 712 effective 16S rRNA gene sequences were obtained, classified into 31 bacterial phyla. One of the highest urease-producing bacterium, Acinetobacter sp. SC4, was then used in consolidation of cracks created in masonry cement mortars. The bio-consolidation led to significant improvement in compressive strength and reduction in water absorption of mortars. It formed calcite observed under scanning electron microscopy, which were in agreement with X-ray diffraction and thermogravimetric analysis. The presented work is the first extensive study on Acinetobacter sp. induced carbonate precipitation in MICP related research. Highlights: Bacterial diversity of a karst cave by Illumina MiSeq sequencing V3-V4 region of the 16S rRNA gene. A total of 58, 712 effective 16S rRNA gene sequences, classified into 31 bacterial phyla. Acinetobacter sp. SC4 was used in consolidation of cracks created in masonry cement mortars. Bio-consolidation resulted in significant improvement in compressive strength of mortars. First report on Acinetobacter sp. induced carbonate precipitation in biocementation research.